Comparison of Personal Guarantees and Collateral in Bank Credit Agreements and Leasing Financing - Dewi, Ida Ayu Cintiya Kencana; Putra, I Made Aditya Mantara (Kertha Patrika, 2025)
This study aims to analyse the effectiveness of guarantees in bank credit agreements and leasing financing, specifically comparing personal guarantees and collateral. Using a normative research method, this study investigates the regulations governing both types of guarantees from the perspective of Indonesian positive law. The objective of this study is to provide a better understanding of when and why each type of collateral should be used, as well as to identify challenges in its application. Through literature studies, analysis of legislation, and a review of court decisions, this study finds that collateral offers greater legal certainty and facilitates execution, especially when the collateral has a stable market value. Conversely, personal guarantees provide flexibility in collateralisation but are highly dependent on the guarantor’s financial capacity and good faith. The results of this study are expected to provide recommendations for legal practice in the field of financing and assist creditors in selecting the optimal type of collateral for their situation.